The Feeding Study of Largehead Hairtail (Trichiurus lepturus) in Oman Sea - I. kamali (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 1999)
Largehead hairtail (Trichiurus leptunts), an important commercially species of the family of Trichiuridae, is found in aboundance in the Persian Gulf and the Oman Sea. The feeding of this fish was studied from November 1995 to October 1996 in Meydani area, a area of the Iranian waters of the Oman Sea which is placed between Jask and Chahbahar parts. Stomach content of 587 specimens of hairtail were studied and classified as full, semifull and empty. The frequency of full, semifull and empty stomachs were 15%, 17% and 68% respectively. Minimum feeding obtained in April and March and maximum in August. The Vacuity index (CV) was 68. I and food prefect (Fp) of stomach content assiged which was tor eaten fishes 70.1%, crustacea 16% and molluscs 13.9%, so fishes were determined as main food. The most frequent food item Of stomach content was anchovey (Stolephorus sp.)